SOCIOCULTURAL CHALLENGES IN TRANSLATING ARABIC GRAFFITI INTO ENGLISH: A PRAGMATIC STUDY - Ibrahim Abdullah Mohammed; Asst. Prof. Kanaan K. Hasan (PhD) (American Journals Publishing, 2024)
Graffiti is a form of communication used by various subcultures to convey personal opinions publicly. It can function as a medium for conveying political, social, and commercial messages. Translating graffiti poses significant difficulties for translators, mainly when dealing with languages from diverse cultural backgrounds. The dataset for this study comprises examples of Arabic graffiti that have been translated into English. Translating Arabic graffiti into English is a significant challenge due to the vast disparities in language and cultural aspects between the two. Translators encounter numerous challenges while translating because of the absence of precise counterparts in the language they are translating into. The objective of this study is to identify the sociocultural impacts on the translation of Arabic graffiti into English, focusing on a pragmatic viewpoint. It also attempts to examine the difficulties associated with dialects, colloquial language, metaphors, and culture-specific terminology. Additionally, it seeks to determine the techniques that translators rely on during the translation process and the level of equivalency they reach. Lastly, the study seeks to determine whether the selection of a particular method for portraying graffiti texts influences the translators' ability to reach equivalence. The present study posits that translators' varied origins and perspectives may lead to subjective interpretations and biases influenced by social, cultural, religious, and political ideologies. The study's conclusion demonstrates that a single technique can result in many equivalence levels within a given translation. Translators encounter various problems, including lexical, semantic, grammatical, pragmatic, structural, textual, contextual, and cultural obstacles, during the translation process.
Keywords: Graffiti, Sociocultural, Pragmatic Perspective, Social Beliefs, Translation Methods.